2019
DOI: 10.21815/jde.019.062
|View full text |Cite
|
Sign up to set email alerts
|

Where Do Pediatric Dental Residents Intend to Practice? Exploring the Influence of Loan Repayment Programs and Other Factors

Abstract: The high cost of dental education and consequent loan burdens contribute to the shortage of pediatric dental providers in rural areas (RAs). Economic incentives are meant to recruit practitioners to RAs. The aim of this study was to assess the ability of government subsidized loan repayment programs (GSLRPs) to recruit pediatric specialists to practice in RAs. A 26‐item questionnaire was emailed to all 921 pediatric dental residents across the U.S. in 2015 for a cross‐sectional study of factors influencing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The literature on location decisions in the medical marketplace supports the notion that physicians and dentists generally choose to establish their practices in more affluent areas [ 105 , 106 , 107 , 108 , 109 , 110 ]. This location behavior may serve to attract private patients to offset the low reimbursement rates of Medicaid [ 28 ], hence counterbalancing costly student loan debt [ 111 , 112 ]. Location decisions may be financially motivated rather than needs-based, thus leading to an inequitable distribution of health providers.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on location decisions in the medical marketplace supports the notion that physicians and dentists generally choose to establish their practices in more affluent areas [ 105 , 106 , 107 , 108 , 109 , 110 ]. This location behavior may serve to attract private patients to offset the low reimbursement rates of Medicaid [ 28 ], hence counterbalancing costly student loan debt [ 111 , 112 ]. Location decisions may be financially motivated rather than needs-based, thus leading to an inequitable distribution of health providers.…”
Section: Discussionmentioning
confidence: 99%
“…17 The amount of funding provided to dental recipients ($50,000) may also contribute to the increased interest in rural practice, falling within the range observed as appealing in previously published work. 6 Future program evaluation that matches samples of applicants and awardees may delineate the influence of actual and perceived rural background, rurality of rotation site location, and program participation, including scholarship amount, on retention of dental providers in the state.…”
Section: Discussionmentioning
confidence: 99%
“…In a study examining pediatric dental residents, researchers concluded that provision of service scholarships of at least $40,000-$60,000 are likely needed for effective recruitment of pediatric dental residents to rural locations. 6 In Georgia, it was found that a medical scholarship's effect on recruitment and retention in rural locations increased when the repayment amount was increased to three times the amount of the original scholarship in lieu of completing the service obligation, and information about and applications for the scholarship were presented during a medical job fair. 7 Service scholarships were found to be important for provider community choice and possible retention in the community.…”
Section: Introductionmentioning
confidence: 99%